(untitled) (Innovative professional education, 2024)
The problem of modelling classes in the educational process of training bachelors in information technology is studied. Successful practices in the framework of competence-based learning used in leading US higher education institutions are analysed, and the most effective methods and forms used for high-quality professional training of IT specialists are identified, which can be further implemented in the domestic practice of training bachelors in information technology.